The Harsh Fight against Poverty in Sao Tome and Principe - Nascimento, Augusto (2009)
Starting, on one side, with a reflection about the history and political vicissitudes of the post-independence, and on the other hand, the testimonies from Sao Tomeans individuals from different social conditions and different degrees of political responsibility, this article approaches some possible connections between poverty and micro-violence in Sao Tome and Principe. It is offered an outline of research for the difficulties of the eradication of poverty and, concomitantly, the diffusion of a growing feeling of social disruption, processes in all contrary to the promises of independence for this archipelago.